Young Christians in Norway, national socialism, and the German occupation of 1940-1945 - Hale, F. (Faculty of Theology, University of the Free State, 2011)
The German occupation of Norway during the Second World War caused unprecedented problems for the Evangelical Lutheran Church of Norway and other Christian denominations. The subordination of the church to the de facto Nazi state eventually led its bishops and most of its pastors to sever their ties to the government while remaining in their ministries. Churchmen and scholars have explored dimensions of this challenging episode in Norwegian church history, but little has been published about the plight of most of the para-church organizations. This article explores crucial dimensions of the ministry of the Norwegian Christian Student Association. Particular attention is paid to how both its pietistic heritage and tradition of social ministry continued to nurture its members and to how the exigencies of living under an oppressive regime compelled the leadership as well as the members of the organization to shift certain emphases in their proclamation and ministry. The predicament of the Church of Norway during the occupation of the country by German forces beginning in April 1940 and with the co-operation of the puppet government of Vidkun Quisling from 1942 until 1945 has long been the subject of scholarly and semi-popular inquiry. Publications about aspects of the general theme began to appear shortly after the end of the Second World War with Hartvig C. Christie’s Den norske kirke i kamp,1 Ingvald B. Carlsen’s Kirkefronten i Norge under okkupasjonen 1940-1045,2 and Ludwig Schübeler’s Kirkekampen slik som jeg så den. Renewed interest in the theological dimensions of the kirkekamp, or struggle of the church, was manifested during the 1970s, especially in Torleiv Austad’s masterly study of pivotal confessional aspects, Kirkens Grunn. Analyse av en kirkelig bekjennelse fra okkupasjonstiden 1940-1945.4More recently, scholars on both sides of the Atlantic have reconsidered the kirkekamp its broader implications. The Swedish church historian Ragnar Norrman published his Quislingkyrkan. Nasjonal Samlings kyrkopolitik 1940-1945 in 1998,5 Pål A. Berg his Kirke i krig. Den norske kirke under 2. verdenskrig the following year,6and in 2005 Austad’s highly useful edition of pertinent documents appeared under the title Kirkelig motstand.7 Awaited is Arne Hassing’s extensive general history of the subject. These works have shed countless photons of light on central matters of the struggle, focusing chiefly on the confrontation between the bishops and other clergymen of the Church of Norway on the one hand and the Quisling administration on the other. Still unilluminated in the published scholarly literature, however, are the role of many other dimensions of Christian life in Norway during the Nazi occupation. Among these are the numerous para-church organizations, both Lutheran and non-Lutheran, which responded to their nation’s travail in a variety of ways. They claimed the allegiance of and were central to the spiritual life of large numbers of adherents of the state church and smaller numbers outside it. No less than the Church of Norway as an organizational ecclesiastical entity, they were compelled to decide whether they were ultimately responsible to God or a government which they believed was illegitimate and an enormous offense to fundamental Christian principles. Most of what has been published about the predicament of the Norwegian churches in the war has been in Norwegian, with a smaller amount in other Scandinavian languages, especially when one considers books and journal articles of a scholarly nature. Exceptions to this generalisation include inter alia articles by Hassing. It thus seems particularly germane to make more aspects of the general topic accessible to readers internationally who cannot read those languages. In the present article I shall take initial steps towards filling one especially noteworthy lacuna in the scholarly literature by considering aspects of the history of the Norwegian Christian Student and School Youth Organisation, or Norges Kristelige Student- og Skoleungdomslag (NKSS). This large para-church body is particularly germane to the history of the kirkekamp, because it had a fairly comprehensive network of local affiliates across much of Norway and by 1940 encompassed many thousands of members, a considerable number of whom joined the active resistance movement. In this article I shall describe the origins and pre-war spiritual and ethical emphases of the NKSS and how some of its members interpreted the rise of the Third Reich during the 1930s, then consider several aspects of the predicament into which the occupation of Norway thrust it, how it coped with this unprecedented situation, and how its proclamation of the Gospel was shaped by the circumstances in which both the leadership and members in general found themselves.
Keywords: Norway; National socialism; Evangelical Lutheran Church; NKSS